Correlates of HIV-related risk behaviors among self-identified heterosexual men who have sex with men (HMSM): national survey of family growth (2002, 2006–2010, and 2011–2017). Issue 12 (1st December 2020) - Abdallah, Iddrisu; Conserve, Donaldson; Burgess, Tiffany L.; Adegbite, Adebukola H.; Oraka, Emeka
ABSTRACT: Self-identified heterosexual men who have sex with men (HMSM) have unique sexual behaviors that may increase their risk of HIV infection. We assessed the correlates of recent sex with other men and HIV-related risk behaviors among HMSM by sex of their sex partners. We analyzed data from the 2002 and 2006–2017 National Survey of Family Growth limited to men who self-identified as heterosexual and reported any anal/oral sex with another man ( N = 787). Prevalence ratios based on logistic regression models determined the association between sociodemographic and behavior variables with reporting a same-sex partner or at least one HIV-related risk behavior with a female sex partner in the last 12 months. Approximately 17.7% and 42.5% of HMSM with recent same-sex partners reported HIV-related risk behaviors with male and female sex partners, respectively. HMSM who reported a recent same-sex partner and an HIV-related risk behavior reported more annual male (Ave = 2.6:95%CI;1.6–3.7) and female (Ave = 5.0:95%CI;3.3–6.8) sex partners than HMSM with a recent same-sex partner who did not report an HIV-related risk behavior [male (Ave = 1.7:95%CI;1.2–2.1) and female (Ave = 1.6:95%CI;1.1–2.1)]. HMSM with recent same-sex partners may engage in HIV-related risk behaviors with men and women concurrently. Further studies should assess gender-specific risk of infection.